Kreativitas Guru PJOK dalam Melaksanakan Pembelajaran pada Masa Pandemi Covid-19 di SMP/MTs Sederajat Se-Kecamatan Keling Kabupaten Jepara Tahun 2021 - AHMAD NOUVAL; Supriyono Supriyono (Indonesian Journal for Physical Education and Sport, 2022)
This study aims to determine the creativity of PESH teachers in carrying out learning process during the COVID-19 pandemic in SMP/MTs in Keling District, Jepara Regency 2021. This study is a qualitative descriptive study using a survey method with purposive sampling techniques of data retrieval through interviews, observation, and documentation. The subjects in this study were principal, student and teachers of PESH SMP/MTs in Keling District, Jepara Regency. The results of this study show that the aspect of the teacher's ability to see the problems before, during and after learning. The conclusion of this study regarding important aspects in the creativity of PESH teachers SMP/MTs throughout Keling District, Jepara Regency in 2021 showed abilities creativity. This can be seen from three aspects, namely the ability of PESH teachers to see and solve problems, to create and apply ideas to overcome problems, accepting attitudes and being open to new things.